Psychometric validation of the nursing professional values scale-revised: Vietnamese version - Huang, Mei-Chih; Pham, Thi-Phuong-Thao (Jurnal Ners, 2024)
Introduction: The Nursing Professional Values Scale has been widely used to assess the professional values of practicing nurses, nursing students, and faculty members across different countries. This study seeks to validate the psychometric properties of the Vietnamese version of the Nursing Professional Values Scale-Revised (NPVS-R). Methods: A quantitative survey was conducted with the questionnaire of NPVS-R version which was converted from English to Vietnamese by three expert translators, followed by a back-translation by three bilingual experts, then three nursing scholars from different regions of Vietnam assessed the language and content validity. Data were collected from 669 nurses through the Vietnamese Nursing Association network and analyzed by using SPSS and AMOS software. The scale was evaluated based on validity of content and construct, and internal consistency. Results: The Vietnamese NPVS-R scale comprises 25 items across four subscales: Caring, Activism, Trust, Professional, and Justice. Confirmatory factor analysis revealed factor loadings between 0.595 and 0.929, with a chi-square value of 955.303. Fit indices (CFI = 0.935, CMIN/DF = 3.605, RMSEA = 0.062) were satisfactory. Cronbach’s alpha was good, ranging from 0.861 and 0.877, and item-to-total correlations spanned 0.501 to 0.775. There exist significant differences of nurses’ perception on the subscales based on their gender, age, and working experience. Conclusions: NPVS-R is a reliable instrument to measure the professional values of nurses in the distinct Vietnamese context and language. It can serve as a valuable tool for nursing care development and competency assessment across various care units in Vietnam and benefit international comparisons.